Sustainable Development Of Tourism – EU Ecolabel Standards Illustrated Using The Example Of Poland - Dziuba, Radosław (Comparative Economic Research. Central and Eastern Europe, 2016)
Tourism, as one of the biggest and fastest growing industries in the world, has an enormous impact on the achievements of the Europe 2020 growth strategy. The main factor influencing its effectiveness, based on achievement of strategy indicators, is tourist infrastructure, which is understood as hotel and restaurant facilities used by tourists coming to a particular area to meet their needs associated with passive and active tourism. To achieve the highest effectiveness in this regard, the European Union has established the scheme of Ecolabel standards, implemented in individual countries through independent certification, compliance with which means that the strategy’s assumptions can be effectively implemented. According to experts, managing a facility in compliance with Ecolabel standards today is an example of innovative hotel management. In addition to the benefits resulting from taking care of the environment, the certification also allows for a reduction of the operating costs of a facility. This paper aims at verifying – through an econometric model – research hypotheses related to the reduction in operating costs of a facility that complies with the certification standards.